Website-Based Business Travel Order Information System Design at BPKH I Medan - Sapitri, Bela; Marsya, Alviona; Siregar, Fitri Handayani (Journal of Computer Science and Informatics Engineering, 2022)
Balai Pemantapan Kawasan Hutan Wilayah I Medan is one of the government organizational units at the Ministry of Environment and Forestry. Where the leadership and employees at BPKH I Medan often travel between cities and outside the city. Making an official travel order (SPPD) at BPKH I Medan is still done simply with manual recording and has not used a special application. This results in being less effective and efficient, both in terms of material and time, there is a loss of official travel data due to poor data storage processes and procedures and takes a long time. -files that have been saved. Therefore, the software is needed to deal with the problem. The proposed system is the Design of a Website-Based Official Travel Order Information System which was built by applying the Unified Modeling Language (UML) method. This Website-Based SPPD Information System Design will make it easier for employees to make SPPD effective, efficient, accurate, and time-saving and will maintain the security of the SPPD file where the file is stored in a special database.